A Study on Smart App Contents for the Management of Little Baseball Team with Real-Time Broadcasting and Record Keeping - Kim, Jae-Wook; ., . (International Journal of Engineering and Technology, 2019)
This paper aims to suggest an app contents that could manage little baseball league as the little baseball is revitalizing in accordance with vitalization of pro baseball league. Along with the popularity of pro-baseball, the interest toward the sports is also increasing. Thus, the number of youth baseball players and amateur baseball players is also increasing. According to Korean Amateur Baseball and Softball Federation in 2016, there are 1722 elementary school players from 97 teams, 2707 middle school players from 102 teams, 2633 high school players from 69 teams and 1054 college players from 31 teams.Â There are 2938 players from 154 teams under Korea Little League Baseball Federation. Also, there are many players who belong to Korea Youth Baseball Federation and Korea Pony Baseball Softball Association.Parents who support children as baseball players put much economic and timely investment and effort for their development. They use Social Network Service(SNS) such as Kakaotalk and Naver Band to share training and game schedules, notices including expenses, game broadcasting and pictures taken during training or contest. However, using general SNS is limited in supporting service specializing in baseball, thus this study suggests an app contents model for smart phone. The application designed in this study considered households that both parents work so that not only parents but also the players could receive information on real-time basis and enabled the management of playersâ€™ record and broadcasting if watching the game is impossible due to personal situation.Â Â